The Combination of Biofertilizer and Organic Fertilizer to Improve Shallot (Allium ascalonicum L.) Production - Widyastuti, R.A. Diana; Hendarto, Kus; Rahmat, Ali; Warganegara, Hayane Adeline; Listiana, Indah; Asmara, Sandi (Journal of Tropical Crop Science, 2021)
Shallot is one of important horticultural crops in Indonesia; shallot consumption per capita is estimated to be 4.6 kg per year. The objective of this study was to evaluate the effect of combining biofertilizer and organic fertilizer on the production of shallot in Sukabanjar village, Pesawaran, Lampung, Indonesia. The study was set up using a randomized completely block design with two factors, biofertilizers and various organic fertilizers, i.e. cow manure, chicken manure, rice straw compost, oyster mushroom baglog. Our study demonstrated that combining biofertilizer and organic fertilizer significantly increased the number, diameter, and fresh and dry weight of tubers of “Bima Brebes” shallot. Shallots treated with biofertilizer combined with oyster mushroom baglog produced the highest tuber yield of 1788 g compared to 282 g in the control.